2004
DOI: 10.1038/sj.ejhg.5201311
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary marker chromosomes in man: parental origin, mosaicism and maternal age revisited

Abstract: The details of all cytogenetic abnormalities diagnosed in the Wessex Regional Genetics Laboratory (WRGL) since 1967 to the present day have been recorded in the Salisbury Treasury of Interesting Chromosomes (STOIC). From this resource, we identified 137 patients with constitutional autosomal supernumerary marker chromosomes (SMC) ascertained in four principal groups: (i) 37% with abnormal phenotypes; (ii) 7% couples with reproductive difficulties; (iii) 47% antenatal diagnoses and (iv) 9% miscellaneous. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 28 publications
5
77
3
3
Order By: Relevance
“…Our predominance of markers derived from chromosome 15, in the few that were further analysed, is entirely in keeping with other reports. 9,22,23 There are no comparable studies on the prevalence of non-21, 13 or 18 mosaic and non-mosaic trisomies, but Forabosco et al 24 found a rate of 0.22/10 000 births. Our rate of 0.86 included the 22% of cases not reported to be detected prenatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our predominance of markers derived from chromosome 15, in the few that were further analysed, is entirely in keeping with other reports. 9,22,23 There are no comparable studies on the prevalence of non-21, 13 or 18 mosaic and non-mosaic trisomies, but Forabosco et al 24 found a rate of 0.22/10 000 births. Our rate of 0.86 included the 22% of cases not reported to be detected prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Marker chromosomes are known to vary widely phenotypically, with apparently normal babies at birth remaining unkaryotyped. [9][10][11] Thus, the prevalence from cytogenetic surveys does not tell us the diagnosed prevalence among babies. On the other hand, the advent of prenatal screening has led to earlier detection of some babies with chromosome abnormalities who would not survive to live births, and to the increased detection of chromosomal abnormalities, which result in phenotypically normal children.…”
Section: Introductionmentioning
confidence: 99%
“…The mother reported a normal development at the age of 6 months. (8). The hybridization signal with the alphoid probe for 8 fully covered the SMC, suggesting the absence of euchromatin.…”
Section: Resultsmentioning
confidence: 99%
“…All had occurred de novo. There were eight cases (61.5%) of heterochromatic (class III) SMCs and of these, five resulted in children without anomalies carrying SMCs 6,8,11,17 …”
Section: Prevalence Of the Cecr And Possible Maternal Age Effectmentioning
confidence: 99%
“…However, there are exceptions to this, such as when there are imprinting effects from uniparental disomy, or low level, tissue specific mosaicism for the sSMC in a parent without phenotypic manifestations (Graf et al, 2006). sSMCs are also classified as satellited or non-satellited and mosaic or non-mosaic (Crolla et al, 2005). It has previously been reported that carrying an accessory bisatellited sSMC was not a risk factor for having abnormal offspring, spontaneous abortion or nondisjunction (Kumar et al, 1997).…”
Section: Discussionmentioning
confidence: 99%